(untitled) (Journal of Business and Technology (Dhaka), 2015)
We investigate the interrelationship between the monthly trade balance and exchange rate data of Bangladesh. We find the existence of cointegration between these two variables. Error correction model reveals that the speed of adjustment coefficient of the trade balance equation corrects about 13% of any deviation from the long-run path within a month with a unidirectional causality running from exchange rate to trade balance. While the speed of adjustment coefficient of the exchange rate equation corrects only 0.003% within a month. This is somewhat slow and statistically insignificant. Journal of Business and Technology (Dhaka) Vol.9(2) 2014; 15-25